The Role of Fintech in Improving Financial Literacy in the Use of E-Wallets of UGJ Management Students in Cirebon City, 2025 - Utami, Ardelia; Shakilla, Raudah; Parlina, Nurhana (Dinasti Publisher, 2025)
The rapid development of information and communication technology has brought significant changes in the financial sector, especially through Financial Technology (Fintech). One of the most popular fintech innovations in Indonesia is E-Wallet or digital wallet, such as DANA, GoPay, and ShopeePay. This study aims to analyse the effect of fintech and E-Wallet on students' financial literacy. Using quantitative methods and a comparative causal approach, this study involved 342 UGJ management students in Cirebon City as respondents selected based on the Slovin formula. Data processing was carried out using the SEM-PLS method to test the causal relationship between variables. The results showed that fintech has a significant effect on students' financial literacy, although with a relatively weak effect size (0.074). Meanwhile, the use of E-Wallets has a greater influence on financial literacy with an effect size of 0.240. However, the moderation of E-Wallet in the relationship between fintech and financial literacy does not prove significant. This indicates that E-Wallet directly contributes to improving students' financial literacy, while the role of fintech in general is still less strong. These findings provide important implications for academics, financial practitioners, and educational institutions to improve financial literacy through the use of E-Wallets and digital education. Campuses are advised to hold seminars and workshops related to more effective digital financial management. Future research is recommended to expand the scope of the study area, consider more E-Wallet platforms, and analyse the security and risk aspects of using E-Wallets.